2006
DOI: 10.1063/1.2186072
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of diamond metal-insulator-semiconductor field-effect transistors with aluminum oxide gate insulator

Abstract: Metal-insulator-semiconductor field-effect transistors (MISFETs) with aluminum oxide as a gate insulator have been fabricated on a hydrogen-terminated diamond surface using its surface conductive layer. The aluminum oxide gate insulator was deposited on the diamond surface by the pulsed laser deposition method. The on-off ratio measured by dc was greater than five orders of magnitude, one of the best results reported for diamond FETs. The gate leak current of aluminum oxide MISFETs is three orders of magnitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…When V d = À0.05 V and V g = ±1 V, this SiO 2 gate showed an I g of about À10 À1 A/mm 2 , which is three orders higher than that for a pulsed laser ablation Al 2 O 3 -gate diamond MOSFET. 23 For a MOSFET with a resistivity heater evaporated SiO insulator on a H-terminated surface of polished polycrystalline diamond with a 12-lm-long, 90-lmwide gate, Kitatani et al 24 reported a maximum normalized I d of À100 lA/mm at V g = À4.75 V, and a maximum g m of 1 mS/mm. They also reported a breakdown voltage of over 200 V, which is considered high enough to achieve a stable oxide.…”
Section: Resultsmentioning
confidence: 99%
“…When V d = À0.05 V and V g = ±1 V, this SiO 2 gate showed an I g of about À10 À1 A/mm 2 , which is three orders higher than that for a pulsed laser ablation Al 2 O 3 -gate diamond MOSFET. 23 For a MOSFET with a resistivity heater evaporated SiO insulator on a H-terminated surface of polished polycrystalline diamond with a 12-lm-long, 90-lmwide gate, Kitatani et al 24 reported a maximum normalized I d of À100 lA/mm at V g = À4.75 V, and a maximum g m of 1 mS/mm. They also reported a breakdown voltage of over 200 V, which is considered high enough to achieve a stable oxide.…”
Section: Resultsmentioning
confidence: 99%
“…The gate and drain voltage changed from + 1 to À 3 V and from 0 to À 8 V, respectively. The CaF 2 gate with 1.1 Am length and 50 Am width used here has the gate leakage current of the order of 10 À 1 A/mm 2 when V d = À 0.05 V and V g = T 1 V, which is three orders higher than in the case of a pulsed-laser ablation Al 2 O 3 -gate diamond MISFET [20]. Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Although boron delta-doped diamond is considered to be a promising channel layer to resolve this issue [7,8], the hole mobility of it is behind expectations. By now, most of the successful diamond-based metal-insulatorsemiconductor field effect transistors (MISFETs) have been fabricated on hydrogenated-diamond (H-diamond) epitaxial layers [9][10][11], which accumulate holes on the surface with sheet hole density of 10 12 -10 13 cm − 2 . Recently, the sheet hole density of the H-diamond was reported to be reached as high as 10 14 cm − 2 by exposing it in NO 2 ambience or by annealing oxygen-terminated diamond in NH 3 and H 2 mixture ambience [12,13].…”
Section: Introductionmentioning
confidence: 99%